On “The Familial Occult.” An Interview1 with Alexandra Coțofană - Alexandra Coțofană; Anamaria Iuga (Martor, 2023)
The interview offers a short insight into the soon to be published book at Berghahn, coordinated by Alexandra Coțofană, “The Familial Occult; Encounters at the Margins of Critical Autoethnography”.